Duplication of the Gallbladder. A Case Report. (2nd November 2009) - Desolneux, G.; Mucci, S.; Lebigot, J.; Arnaud, J. P.; Hamy, A.
Abstract : Gallbladder duplication is a rare anatomic malformation, which can now be detected by preoperative imaging study. We report a case of a symptomatic duplicated gallbladder, successfully treated by laparoscopic cholecystectomy. This anomaly is important to know for surgeons because of associated anatomical variations of main bile duct and hepatic artery and increased risk of common bile duct injury.